Full‐layer mucosal histology in achalasia: Histological epithelial wave is characteristic in "pinstripe pattern"‐positive achalasia. Issue 1 (26th July 2017) - Sato, H.; Takahashi, K.; Nakajima, N.; Hasegawa, G.; Mizuno, K.; Hashimoto, S.; Ikarashi, S.; Hayashi, K.; Honda, Y.; Yokoyama, J.; Sato, Y.; Terai, S.
Abstract: Background: Previously, the mucosal histology in achalasia has only been investigated using superficial biopsy or surgically resected esophageal specimens in end‐stage cases. We investigated the histology of the full‐layer mucosa in early and advanced achalasia. Methods: Endoscopy was performed for the pinstripe pattern (PSP) (an early achalasia indicator) and dilation and thickening of the mucosa (advanced achalasia indicators). A mucosal entry site for peroral endoscopic myotomy was created using cap‐fitted endoscopic mucosal resection to access the full‐layer mucosa and the submucosa. Key Results: Mucosal histology was compared between 32 patients with achalasia and 15 controls. Histological esophagitis with findings of inflammatory cell infiltration and dilated intercellular spaces was observed more in patients with achalasia than in controls (87.5% vs 13.3%, P <.001; 84.4% vs 46.7%, P =.049). Muscularis mucosae (MM) atrophy and epithelial wave were only observed in achalasia (40.6% vs 0%, P =.005; 28.1% vs 0%, P =.043). Fibrosis was more common in achalasia, but without statistical significance (31.3% vs 20.0%, P =.503). In achalasia with endoscopic dilation and thickening of the mucosa, MM atrophy was observed histologically, and in cases involving endoscopic PSP, the histological epithelial wave was observed. Conclusions & Inferences: Histological findings of esophagitis were observed endoscopically even in early achalasia. Pinstripe pattern corresponds to the epithelial wave observed histologically in achalasia, whereas endoscopic findings in advanced achalasia correspond to MM atrophy. Appropriate management is necessary during early achalasia to prevent progression to advanced achalasia with more severe histological changes. Abstract : The pinstripe pattern on endoscopy corresponds to histological epithelial wave, and endoscopic findings of advanced achalasia are related to histological muscularis mucosae atrophy. Appropriate management is necessary during early achalasia to prevent progression to advanced achalasia with more severe histological changes.